Halogen Bonding Involving Gold Nucleophiles in Different Oxidation States - Aliyarova, Irina S; Tupikina, Elena Yu; Soldatova, Natalia S; Ivanov, Daniil M; Postnikov, Pavel S; Yusubov, Mekhman; Kukushkin, Vadim Yu (Inorganic chemistry, 2022)
A single-crystal X-ray diffraction (XRD) study of diaryliodonium tetrachloroaurates (or, in the recent terminology, tetrachloridoaurates), [(p-XC6H4)2I][AuCl4] (X = Cl, 1; Br, 2), was performed for 1 (the structure is denoted as 1a to show similarity with the isomorphic structure 2a) and two polymorphs─2a (obtained from MeOH) and 2b (from 1,2-C2H4Cl2). Examination of the XRD data for these three structures revealed 2-center C-X···AuIII (X = Cl and Br) and 3-center bifurcated C-Br···(Cl-Au) halogen bonding (abbreviated as XB) between the p-Cl or p-Br atoms of the diaryliodonium cations and the gold(III) atom of [AuCl4]-. The noncovalent nature of AuIII-involving interactions, the nucleophilicity of the gold(III) atoms, and the electrophilic role of p-X atoms of the diaryliodonium cations in the XBs were studied by a set of complementary computational methods. Combined experimental and theoretical studies allowed the recognition of the d-nucleophilicity of the [d8AuIII] atom which, regardless of its rather substantial formal 3+ charge, can function as a d-nucleophilic partner of XB. This conclusion was also supported by theoretical calculations performed for the structures' refcodes BINXOM and ICSD 62511; the obtained data verified the nucleophilicity of AuIII toward a K+ ions or a σ-(Cl)-hole, respectively. All our results, together with consideration of relevant literature, indicate that gold atoms in the three oxidation states (0, I, and even III) exhibit nucleophilicity in XBs.